Безпосередня демократія під час війни: за та проти - Тарабанов, О. Ю.; Tarabanov, O. Yu.; Філіпська, Н. О.; Filipska, N. O.; Nataliia Filipska (Innovative development оf science, technology and education». V International Scientific and Practical Conference (Vancouver, Canada, 15-17 лют. 2024 р.). - Vancouver, 2024. - С. 604-610, 2024)
Дана робота присвячена проблемі забезпечення принципу змінності влади в умовах надзвичайних станів, зокрема, воєнного стану. Проаналізовано досвід держав щодо проведення виборів до органів державної влади в умовах збройного конфлікту. Аргументовано висновки щодо значного ускладнення проведення виборів глави держави в Україні у існуючих умовах повномасштабної війни, окупації значної території держави та відсутності достеменних даних щодо громадян, які виїхали з держави.

This work is devoted to the problem of ensuring the principle of alternation of power in conditions of emergency, in particular, martial law. The experience of states in holding elections to state authorities in conditions of armed conflict is analyzed. The conclusions are argued regarding the significant complication of holding elections of the head of state in Ukraine in the existing conditions of full-scale war, occupation of a significant territory of the state and the lack of reliable data on citizens who have left the state.
Keywords: воєнний стан; збройний конфлікт; безпосередня демократія; принципи демократії; безпека; martial law; armed conflict; direct democracy; principles of democracy; security